The Implementation of the Know-Want-Learned (KWL) Learning Strategy Using Puzzle Media to Improve the Quality of Indonesian Language Learning for Grade VI Students at SD Negeri 30 Bilah Barat, Labuhan Batu Regency, Academic Year 2025-2026 - Arika Ritonga; Sutikno; Rahmat Kartolo (International Journal of Educational Research Excellence (IJERE), 2026)
This study aims to determine the effectiveness of the application of the Know Want Learned (KWL) learning strategy in improving the quality of Indonesian language learning through puzzle media for sixth grade students of SD Negeri 30 Bilah Barat, Labuhan Batu Regency, Academic Year 2025-2026. This type of research is Classroom Action Research (CAR) which is carried out in two cycles, each consisting of four stages: planning, implementation, observation, and reflection. The subjects of this study were sixth grade students of SD Negeri 30 Bilah Barat, while the object of this research was improving the quality of Indonesian language learning, especially in the ability to understand narrative texts. The instruments used to collect data were observation sheets and written tests given to students. The results of the study showed that the application of the KWL strategy with puzzle media can improve the quality of Indonesian language learning. This can be seen from the increase in student learning activities recorded in cycle I by 72.5% and increased to 85.3% in cycle II. In addition, student learning outcomes also increased, which is reflected in test scores that showed classical completeness in cycle I by 70% and in cycle II reaching 88%. Thus, the implementation of the KWL strategy with puzzle media is not only able to increase students' learning activities, but also strengthen their understanding of the material being taught. Based on these findings, it can be concluded that the implementation of the KWL strategy with puzzle media is effective in improving the quality of Indonesian language learning for sixth-grade students of SD Negeri 30 Bilah Barat, Labuhan Batu Regency, both in terms of learning activities and learning outcomes obtained